Phase Morphology Evolution and Rheological Behavior of Toughened Polypropylene Composite with Controllable Brittle–Ductile Transition Temperature Using SEPS@HDPE Core–Shell Structure - Jiahao Shen; Zhiyi Zhang; Wenwen Yu; Jiayi Wang; Weixuan Wang; Yonggang Shangguan; Qiang Zheng (Engineering)
The toughness of thermoplastic polymers such as polypropylene (PP) can be improved by adding elastomers-based toughening agents, and the phase morphology of these toughening agents is very important for the strength and toughness of PP. The low-temperature toughness of PP was improved by inserting high-density polyethylene (HDPE) between PP and polystyrene-b-ethylene-co-propylene-b-polystyrene (SEPS) to form an unusual SEPS@HDPE core–shell structure, with SEPS as the core and HDPE as the shell. Based on the microtopography and rheological behavior characterization, HDPE in PP/SEPS/HDPE composites was found to serve as an emulsifier, decrease the size of SEPS particles, and promote the homogeneous dispersion of dispersed phase particles in the matrix. An increase in the HDPE content shifted the toughening mechanism of PP composites from cavitation to matrix shear yielding. The reduction in the distance between the dispersed core–shell structure particles promoted shear yielding in the PP composites, leading to increased toughness. The creation of an intermediate HDPE layer with a moderate modulus was crucial for dispersing stress concentrations and significantly improving toughness without compromising the tensile strength. These findings will facilitate the fabrication of high-toughness PP products at low temperatures.